Causal Loop Diagram for Analysis System Dynamics: The Role of Communication Technology in Strengthening Global Muslim Identity - Rahmaniar, Yusi; Nasution, Satri Dwi Kurnia (Al-madinah: Journal of Islamic Civilization, 2025)
This study investigates the complex ways in which communication technology influences the development and strengthening of a global Muslim identity. The research employs a system dynamics approach, utilizing the Causal Loop Diagram (CLD) methodology to construct a comprehensive visual model. This model systematically illustrates the interconnected variables and intricate feedback mechanisms that drive this contemporary phenomenon. The CLD reveals how the widespread proliferation of diverse digital platforms and social media channels enables the rapid and far-reaching dissemination of religious discourses. This process, in turn, fosters the organic emergence of robust online Muslim communities, creating a dynamic cycle. The model further elucidates how these online communities and their interactions contribute to a heightened sense of shared identity and collective consciousness, particularly when operating within broader socio-political contexts. Through a detailed analysis of these dynamic interdependencies, the study identifies critical leverage points for positive change and also highlights potential unforeseen outcomes associated with the powerful role of technology in shaping a unified global Muslim identity. The principal findings point to a powerful reinforcing feedback loop where increased online engagement leads directly to a more cohesive community, which subsequently drives even greater participation and a stronger sense of transnational belonging. The major conclusion is that communication technology acts as a fundamental catalyst for a new form of religious identity that transcends geographical borders. Ultimately, the study's contributions offer valuable and timely insights for both scholars and policymakers seeking to comprehend the evolving nature of religious identity in the digital era and its broader societal implications.